Pengaruh pupuk daun Gandasil D terhadap pertumbuhan, kandungan klorofil dan karotenoid tanaman bayam merah (Alternanthera amoena Voss.) - Fetryani Soni Manurung; Yulita Nurchayati; Nintya Setiari (Jurnal Biologi Tropika, 2020)
Red spinach is (Alternanthera amoena Voss.) a vegetable that contains vitamins (vitamin A, C, and E) and minerals.Yield optimization red amaranth cultivation can be done with additional supplementary fertilizer like fertilizer leaves Gandasil D. The purpose of this study are to examine the effect of Gandasil D fertilizer on vegetative growth of plants and determine the optimal concentration of Gandasil D fertilizer on the chlorophyll and carotenoid content of the leaves. The experiment was carried out by germinating red spinach seeds, transferring 14 -days-old seedlings into pots containing planting media and basic fertilizers.  Seedlings at 14-days-old were then given Gandasil D fertilizer by spraying on the surface of the leaves once a week until the age 32–days-old. The study was conducted with a CRD with a single factor with 4 treatments of Gandasil D concentration, namely 0g/L (control), 1g/L, 2g/L, and 3g/L with 5 replications.  Parameters observed that the number of leaves, plant height, root length, wet weight, dry weight, chlorophyll, and carotenoid content.  Data were analyzed by ANOVA followed by Duncan’ test at the 95% significance level. The results showed that the application of Gandasil D significantly affected the number of leaves, plant height, and fresh weight of the plant.  Spraying with Gandasil D did not show a significant effect on root length, plant dry weight, and chlorophyll and red spinach carotenoid content.  Gandasil D fertilizer at a concentration of  3g/L produces the most optimal growth of red spinach plants.